WOUNDS SPEAK: TRAUMA IN THE POETRY OF CZESLAW MILOSZ. - JOHNY, NIDHIN. (IISER Mohali, 2024)
The thesis attempts a reading of the Polish American Nobel Laureate, Czeslaw Milosz’s poetry from the perspective of literary trauma studies. A poet, translator, essayist, and verse novelist, Milosz began his literary journey from Poland, and owing to political reasons, he defected to the West. Milosz’s poems dealt with themes such as governmental repressive mechanisms and the censorship of his works. Choosing Milosz’s New and Collected Poems 1931-2001, this thesis looks at how the places and geographical features participate in the expression of the trauma of exile. The loss of homeland is an important event in the life of the poet, and by resorting to the use of various cities, forests, and rivers in the poems, the poet captures the trauma of this loss. The harsh imposition of censorship impacted the literary career of the poet, and the thesis investigates the choice of the Polish language as a form of resistance and the poet’s use of inner censorship to circumvent the suppression of the voices of dissent. Mythological narration is yet another indispensable part of his poems. Using Greek and Eastern European myths, the poet uniquely addresses the question of trauma. Contributing to the existing literary repertoire of trauma studies from these perspectives, this thesis situates such traumatic experiences in the larger socio-cultural and historical context.
Keywords: POETRY.; WOUNDS SPEAK.; TRAUMA.